محاكاة الخلية البشرية - ميساء أبوقاسم; زهير الشهابي; فراس صالح (Tishreen University, 2018)
في نموذجنا الخليوي المسمى SYRIA تم تطوير نموذج لمحاكاة عمل خلية عضلية قلبية بطينية باعتبارها مثالاً عن محاكاة الخلية البشرية، وذلك بالاعتماد على أحدث النماذج الرياضية للخلية القلبية، حيث اعتمدنا على  O'Hara (1) لنمذجة النشاط الكهربائي، واستتباب الشوارد الأساسية، والتقلص، كما تم اضافة تحسينات على هذا النموذج تمثلت في إضافة دور قنوات البوتاسيوم KATP، وقنوات شوارد الكلور، وقنوات تنظيم الحجم، وذلك بالاعتماد على نموذج  Kyoto (2)، كما تم إضافة قنوات تنظيم واستتباب PH بالاعتماد على نموذج Leem (3)، وتم ربط النماذج السابقة مع نموذج للمتقدرة بالاعتماد على Kembro (4)، إذاً النموذج SYRIA  الذي طورناه يعتمد على دمج وتحسين أهم النماذج المعروفة في بنية هرمية تسهل الفهم والمراقبة واعادة الاستخدام مع إضافة نماذج لاختبار العقاقير وبعض المؤثرات الخارجية، وتمت عملية البرمجة باستخدام كتل Blocks لتوابع  M-file وS-function ضمن الأداة  Simulink. وبمقارنة النتائج التي حصلنا عليها من عملية المحاكاة مع النتائج المخبرية، لوحظ أن المحاكاة الحاسوبية أعطت نتائج  ضمن المجال الفيزيولوجي الطبيعي. In this paper, we present a state-of-art model, we call SYRIA, to simulate the activity of ventricular myocardial cell  as an example of  simulating a human cell, in which we use  the latest mathematical models of cardiac cell. We rely on O'Hara (1) for modeling electrical activity, ions hemostasis, and contracting. Our presented model takes into consideration the role of potassium channels KATP, chloride channels, volume regulation channels based on the Kyoto model (2), PH regulation channels based on Leem model (3). The previous models have been linked to a Mitochondrial model  based on Kembro (4). The SYRIA model is based on the integration and improvement of the best known models in a hierarchical structure that facilitates understanding, monitoring and reuse,  we also present models for testing drugs and some external influences. The programming process is done using blocks of M-file and S-function in Simulink. By comparing the results obtained from the simulation with the laboratory results, we observe that computer simulations give results within the normal physiological range.